Побудова альтернативної системи рейтингування наукової активності вищих навчальних закладів України: методичні засади та результати апробації - Раєвнєва, Олена Валентинівна; Степуріна, Світлана Олександрівна (НВП ПП "Технологічний Центр", 2017)
Стаття присвячена розробці альтернативної системи рейтингування наукової активності вищих навчальних закладів (ВНЗ) України. Структура системи містить два рівні: рівень формування однорідних за ступенем наукової продуктивності кластерів ВНЗ та рівень визначення рейтингової позиції ВНЗ по кожному кластеру. Відмінністю запропонованої рейтингової системи є використання обґрунтованого переліку відносних показників в якості індикаторів рейтингового оцінювання, що дозволяє елімінувати ефект "масштабу виробництва" ВНЗ.

Higher school conditions the direction of the social development by introducing scientific ideas, developing innovative technologies, studying and promoting effective socio-economic mechanisms of the country development, supports the cultural level, intellect and spirituality of the society. That is why the creation of conditions for strengthening main directions of the higher educational institutions (HEI) activity, especially, their scientific-research, scientific-technical and innovative potential it is a key task of the higher educational system modernization by the Ministry of education and science (MES) of Ukraine. On the background of diverse factors of such motivations, the one of importance is the factor of comparative collations that is the rating base. The article is devoted to the further development of methodological principles, methodical and information-model support of the construction of the rating system of the assessment of the Ukrainian higher educational institutions potential. The special feature of the offered rating system is the formation of the multi-component system of the quality monitoring of the HEI scientific activity by the four main factors: international activity, scientific activity, citing and commercialization of scientific results. Local indicative systems that allow to assess the HEI scientific activity from system positions were formed for each factor, based on the comparative analysis of the list of parameters of the well-known world ratings and features of the Ukrainian higher system modernization. The pilot calculations of the scientific activity of Kharkiv HEI were realized to probate the offered rating assessment system.
Alternative rating system of scientific activity of Ukrainian higher educational institutions: methodical bases and results
Keywords: ВНЗ; рейтинг; індикативний простір; інтегральний показник; кластерний аналіз; HEI; rating; indicative space; integral parameters; cluster analysis